Health-related quality of life after 6-month post-injury on severe traumatic brain injury: A cohort study in two Malaysia hospitals - Ludin, Salizar; Rashid, Nor'ain (Elsevier, 2019)
Objective: Severe traumatic brain injury (TBI) survivors show physical and functional improvement but remain with the cognitive and psycho-social problem through our recovery. This study aims to measure the health-related quality of life of TBI survivors within 6 months post-injury. Method: A cohort study was conducted where 33 severe TBI survivors recruited at two tertiary hospitals. The health-related quality of life was measured using the Quality of Life after Brain Injury (QOLIBRI) tool. Results: Participants mean age was 31.79 years old. The impaired range of health-related quality of life on 6 months post-injury seen, but an improvement occurs within 3---6 months post-injury. Conclusions: Age and ventilation duration showed a moderate negative correlation in all domains and length of hospital stay showed a moderate negative correlation to social, daily life and self-domains. Nevertheless, small sample size and time constraint were the limitations of this study.